Nyadran dalam perspektif ‘urf : studi tradisi perkawinan di desa balun kecamatan turi kabupaten lamongan - Natasya, Alvionita Nefa (Maliki Interdisciplinary Journal, 2024)
This article aims to describe the views of the people of Balun Village towards the nyadran tradition and to analyze the nyadran tradition from the perspective of ’urf. This article is an empirical juridical study using a qualitative approach. Data were obtained from interview results. Data and data sources in this article are primary data sources and secondary data sources. Meanwhile, the data processing used consists of four stages: data examination, classification, data analysis, and conclusions. The results of this article are as follows: 1) The views of the Balun Village community on the nyadran tradition, which is still practiced to this day, have good intentions and purposes because it is a form of respect for ancestors or pilgrimage to the Saints of God and as an expression of gratitude to the Almighty. 2) The nyadran tradition, when viewed from the perspective of ’urf, includes ’urf shahîh and ’urf fâsid. It is said to be ’urf shahîh because in its implementation process, reading verses of the Qur’an and other prayers are involved. It is said to be ’urf fâsid because during the implementation of the nyadran tradition, it involves bringing tumpeng (cone-shaped rice dish), bringing wedding clothes, and believing that if nyadran is not performed, there will be consequences. This contradicts Islamic law. Therefore, the tradition can be preserved if the community is able to eliminate such practices.